2009
DOI: 10.1080/19390210802690191
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence-Based Systematic Review of Green-Lipped Mussel (Perna canaliculus) by the Natural Standard Research Collaboration

Abstract: A blinded review is conducted by multidisciplinary research-clinical faculty at major academic centers with expertise in epidemiology and biostatistics, pharmacology, toxicology, CAM research, and clinical practice. In cases of editorial disagreement, a three-member panel of the Editorial Board addresses conflicts, and consults experts when applicable. Authors of studies are contacted when clarification is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…Full-text articles assessed for eligibility (n =184) 37,54 perinatal stroke, acute myocardial infarction, congestive heart failure, 54 severe multiorgan hypoxic injury, 22 carcinoma, 33,61 perforation of the gastrointestinal tract, 61 seizures and epilepsy. 58 The large number of included SRs means that it is not easy to provide practical guidance through this labyrinth of HMs and multitude of AEs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Full-text articles assessed for eligibility (n =184) 37,54 perinatal stroke, acute myocardial infarction, congestive heart failure, 54 severe multiorgan hypoxic injury, 22 carcinoma, 33,61 perforation of the gastrointestinal tract, 61 seizures and epilepsy. 58 The large number of included SRs means that it is not easy to provide practical guidance through this labyrinth of HMs and multitude of AEs.…”
Section: Resultsmentioning
confidence: 99%
“…26 Thirty-one SRs concluded that the HM in question was safe. [13][14][15][16][17][18][19][20][21][23][24][25][26]29,31,32,35,38,39,[42][43][44][45]47,50,53,55,[57][58][59][60] Fifteen SRs reported moderately severe AEs, 12,22,27,28,30,36,40,41,46,48,49,51,52,54,56 and four SRs concluded that the HM in question was not safe (see Supplemental Tables S1 and S2). 33,34,37,…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…osteoarthritis/rheumatoid arthritis and asthma are well covered in a series of reviews(Brien, Prescott, Coghlan, Bashir, & Lewith, 2008;Cobb & Ernst, 2006;Coulson, Palacios, & Vitetta, 2015;Grienke, Silke, & Tasdemir, 2014;Ulbricht et al, 2009). Presently, there are no stud-…”
mentioning
confidence: 99%